Sodium-electrode layered oxide positive electrode active material and application thereof
By phosphate-lanthanum-based substrates, a stable sodium-electric layered oxide positive electrode material is formed, which solves the structural degradation and air sensitivity of the positive electrode material of sodium ion battery, and improves the long cycle stability and electrochemical performance, which is suitable for commercial promotion.
Patent Information
- Application Number
- CN202510417498.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-07-04
AI Technical Summary
The layered cathode materials of existing sodium ion batteries are prone to grain boundary rupture and electrolyte side reactions during the circulation process, resulting in structural degradation and electrochemical performance degradation, and the material's air sensitivity affects the stability of long cycles.
The sodium-nickel-cobalt-manganese-based substrate is coated with phosphate lanthanum materials to form a LaAl(PO4)2, La3Li3(PO4)4 or LaFe(PO4)2 coating layer. By controlling the mass ratio of the substrate material to the coating material, calcining is performed to form a stable sodium-electric layered oxide positive electrode active material.
It significantly improves the structural stability and long circulation performance of the positive electrode material of sodium ion battery, improves the air stability and electrochemical performance of the material, reduces production costs, and is suitable for large-scale commercial applications.
Smart Images

Figure CN120261536A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and particularly relates to a sodium-based layered oxide cathode active material, a cathode material, and a sodium-ion battery. Background Art
[0002] To solve the problems of the limitations of new energy power generation in terms of time and space and improve the utilization rate of new energy, the importance of energy storage technology has become increasingly prominent. Among them, sodium-ion batteries have attracted wide attention due to their advantages such as rich raw materials, low resource cost, safety, and environmental friendliness.
[0003] With the research and development of sodium-ion batteries in recent years, exploring cathode materials with good electrochemical performance is an important way to accelerate the commercial progress of sodium-ion batteries. Currently, the mainstream research directions of sodium-ion battery cathode materials are divided into three categories: layered transition metal oxides, polyanion compounds, and Prussian blue / white compounds. The layered oxide cathode material is characterized by a relatively high specific capacity and a relatively mature technical route, and its production process is similar to that of lithium batteries, enabling faster commercial mass production. However, most layered oxide materials are polycrystalline materials composed of aggregated primary particles. This unique crystal structure is prone to grain boundary rupture during cycling, resulting in side reactions with the electrolyte, thereby reducing the electrochemical performance; it is also prone to react with air during preparation and storage, leading to structural degradation and alkalization, affecting subsequent processing and battery cycling performance.
[0004] Therefore, how to provide a suitable method to solve the air sensitivity problem of the layered cathode material of sodium-ion batteries, improve its structural stability to enhance long-cycle stability and reduce production costs, has become an urgent technical problem for those skilled in the art. Summary of the Invention
[0005] To solve the problem of insufficient long-cycle stability existing in the existing sodium-ion battery cathode materials, the present invention provides a sodium-based layered oxide cathode active material, a cathode material, and a sodium-ion battery.
[0006] The present invention is implemented by the following technical solutions:
[0007] A sodium-based layered oxide cathode active material, and its preparation method is as follows:
[0008] Mix the nickel-cobalt-manganese series precursor Ni a Co b Mn c (OH)2 and the sodium source material by grinding and mixing at a molar ratio of 1:(0.8 - 1.1), calcine at a temperature of 700 - 800 °C in an oxygen atmosphere for not less than 24 h, and after natural cooling to room temperature, grind and sieve to obtain the matrix material; where a + b + c = 1.
[0009] According to the composition of LaAl(PO4)2, La3Li3(PO4)4 or LaFe(PO4)2; adding La 3+ source material, PO4 3- source material and any one of aluminum nitrate, lithium acetate, and iron sulfate into absolute ethanol, and ultrasonically mixing evenly to obtain a suspension for forming a coating material.
[0010] According to the mass ratio of the matrix material to the coating material of 1:(0.0001 - 0.05), add the matrix material to an appropriate amount of the suspension; fully stir until the ethanol evaporates, then vacuum dry and grind into a powder; finally, calcine at a temperature of 520 - 580 °C in an oxygen atmosphere for no less than 6 h to obtain the required sodium-ion layered oxide cathode active material.
[0011] As a further improvement of the present invention, the composition of the matrix material is Na x Ni a Co b Mn c O2, 0.8 ≤ x ≤ 1, a + b + c = 1.
[0012] As a further improvement of the present invention, the coating material used is LaAl(PO4)2.
[0013] As a further improvement of the present invention, the nickel-cobalt-manganese series precursor Ni a Co b Mn c (OH)2 adopts any one of NCM622, NCM811, NCM424, and NCM523.
[0014] As a further improvement of the present invention, the sodium source material adopts NaOH or Na2CO3.
[0015] As a further improvement of the present invention, La 3+ source material adopts any one of lanthanum nitrate hexahydrate, lanthanum chloride, lanthanum sulfate, lanthanum oxide, or lanthanum acetate.
[0016] As a further improvement of the present invention, PO4 3- source material adopts any one of phosphoric acid, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, or phosphorus pentoxide.
[0017] As a further improvement of the present invention, the coating material is prepared from lanthanum nitrate hexahydrate, aluminum nitrate, and ammonium dihydrogen phosphate according to a molar ratio of 1:1:2.
[0018] As a further improvement of the present invention, the heating rate during the calcination of the matrix material and the final product is 5 °C / min.
[0019] As a further improvement of the present invention, the temperature of the matrix material and the suspension during the stirring stage is controlled at 50-60°C, and the temperature during the vacuum drying stage is controlled at 80-85°C.
[0020] As a further improvement of the present invention, the sodium-ion layered oxide cathode active material contains a matrix material and its surface coating material, and the mass ratio of the two is 1:(0.0001-0.05). The composition of the matrix material is Na x Ni a Co b Mn c O2, 0.8≤x≤1, a + b + c = 1, O3 phase structure; the composition of the coating material is LaAl(PO4)2, La3Li3(PO4)4 or LaFe(PO4)2.
[0021] The present invention also includes a cathode material for a sodium-ion battery, which is uniformly mixed by polyvinylidene fluoride, acetylene and the sodium-ion layered oxide cathode active material as described above in a ratio of 6:6:88.
[0022] The present invention also includes a sodium-ion battery, which uses a metal sodium sheet as the counter electrode; uses glass fiber as the separator; uses a solution of ethylene carbonate and diethyl carbonate with a volume ratio of 1:1 containing 1 mol / L sodium perchlorate as the electrolyte. And the slurry corresponding to the cathode material of the sodium-ion battery as described above is coated on the aluminum foil and made into a pole piece after vacuum drying; the mass loading of the sodium-ion layered oxide cathode active material in the pole piece is 3.0±0.15 mg cm -2 。
[0023] The technical solution provided by the present invention has the following beneficial effects:
[0024] In the present invention, by using lanthanum phosphates (such as lanthanum aluminum phosphate, lanthanum lithium phosphate and lanthanum iron phosphate) as the coating material to coat the sodium-nickel-cobalt-manganese-based substrate of the sodium-ion battery cathode active material, the structural stability and long cycle performance of the sodium-ion cathode active material are significantly improved. The surface coating provided by the present invention will not damage the original layered structure of the substrate, can promote the interfacial ion charge transfer, and reduce the occurrence of side reactions, which is one of the most effective strategies to solve such problems.
[0025] In the cathode active material provided by the present invention, PO4 in the coating material 3- will reduce the surface residual alkali of the substrate, improve the air stability of the material, reduce the contact between the material and the electrolyte, and thus improve the processing and cycle performance of the cathode material; La 3+ 、Al 3+ 、Li + and Fe 3+They all belong to ionic conductor elements. The appropriate introduction of them into the coating material can improve the discharge capacity while achieving the benefit of stabilizing the crystal structure; there may be a small amount of La during the preparation process of the coating layer 3+ , Al 3+ , Li + and Fe 3+ are embedded in the transition metal oxide layer in the form of doping. Their relatively large particle sizes will broaden the diffusion channels of Na + , enhance the diffusion kinetics of Na + ; Al 3+ , Li + and Fe 3+ will all play a role in inhibiting the redox activity of Mn 3+ / 4+ in the matrix material to achieve the inhibition of the Jahn-Teller effect caused by Mn 4+ / Mn 3+ ; at the same time, the idea of stabilizing the phase structure and improving the electrochemical performance through inexpensive Al, Li, and Fe elements is an economical, efficient, and environmentally friendly modification idea, which accelerates the commercialization process of the cathode material for sodium-ion batteries.
[0026] The sodium-based layered oxide cathode active material provided by the present invention not only has excellent product performance, but also has a simple preparation process and low manufacturing cost of the product, and is suitable for large-scale popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 FIG. is the SEM image of the sodium-based layered oxide cathode active material prepared by the present invention in the test experiment at a scale of 3 μm.
[0028] Figure 2 FIG. is the SEM image of the sodium-based layered oxide cathode active material prepared by the present invention in the test experiment at a scale of 1 μm.
[0029] Figure 3 FIG. is the TEM image of the cathode material after LaAl(PO4)2 coating prepared by the present invention in the test experiment. DETAILED DESCRIPTION OF THE INVENTION
[0030] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] This embodiment provides a novel sodium-layered oxide cathode active material that uses lanthanum phosphates (such as lanthanum aluminum phosphate, lanthanum lithium phosphate, and lanthanum iron phosphate) as coating materials to coat a sodium-nickel-cobalt-manganese-based substrate. And a preparation process for this novel electrode material is provided. Specifically, the sodium-layered oxide cathode active material contains a matrix material and its surface coating material, and the mass ratio of the two is 1:(0.0001 - 0.05). The composition of the matrix material is Na x Ni a Co b Mn c O2, 0.8 ≤ x ≤ 1, a + b + c = 1, with an O3 phase structure; the composition of the coating material is LaAl(PO4)2, La3Li3(PO4)4, or LaFe(PO4)2.
[0032] The preparation method of this sodium-layered oxide cathode active material is as follows:
[0033] Grind and mix the nickel-cobalt-manganese series precursor Ni a Co b Mn c (OH)2 and the sodium source material in a molar ratio of 1:(0.8 - 1.1), calcine at a temperature of 700 - 800 °C in an oxygen atmosphere for no less than 24 h. After natural cooling to room temperature, grind and screen to obtain the matrix material; the composition of the matrix material is Na x Ni a Co b Mn c O2, 0.8 ≤ x ≤ 1, a + b + c = 1. Specifically, among the nickel-cobalt-manganese series precursors Ni a Co b Mn c (OH)2 in the preparation process of the specific matrix material, any one of NCM622, NCM811, NCM424, and NCM523 can be used. And the sodium source material uses NaOH or Na2CO3.
[0034] According to the composition of LaAl(PO4)2, La3Li3(PO4)4, or LaFe(PO4)2; add the La 3+ source material, PO4 3- source material and any one of aluminum nitrate, lithium acetate, and iron sulfate to anhydrous ethanol and ultrasonically mix evenly to obtain a suspension for forming the coating material. Specifically, among the coating materials, the La 3+ source material can use any one of lanthanum nitrate hexahydrate, lanthanum chloride, lanthanum sulfate, lanthanum oxide, or lanthanum acetate. And the PO4 3- source material can use any one of phosphoric acid, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, or phosphorus pentoxide.
[0035] Add the matrix material to an appropriate amount of suspension according to the mass ratio of the matrix material to the coating material of 1:(0.0001 - 0.05); stir thoroughly at a temperature of 50 - 60 °C until the ethanol evaporates, then vacuum dry at a temperature of 80 - 85 °C and grind into a powder; finally, calcine at a temperature of 520 - 580 °C in an oxygen atmosphere for no less than 6 h to obtain the required sodium-ion layered oxide cathode active material.
[0036] Example 1
[0037] Grind and mix the nickel-cobalt-manganese series precursor NCM622 and the sodium source NaOH in a molar ratio of 1:1.05, place them in a tube furnace, and calcine at 700 °C for 24 h in an oxygen atmosphere with a heating rate of 5 °C / min. After natural cooling to room temperature, grind and pass through a 325-mesh sieve to obtain the No. 1 substrate, denoted as NaNi 0.6 Co 0.2 Mn 0.2 O2.
[0038] Grind and mix the nickel-cobalt-manganese series precursor NCM811 and the sodium source NaOH in a molar ratio of 1:1.1, place them in a tube furnace, and calcine at 800 °C for 24 h in an oxygen atmosphere with a heating rate of 5 °C / min. After natural cooling to room temperature, grind and pass through a 325-mesh sieve to obtain the No. 2 substrate, denoted as NaNi 0.8 Co 0.1 Mn 0.1 O2.
[0039] Grind and mix the nickel-cobalt-manganese series precursor NCM424 and the sodium source Na2CO3 in a molar ratio of 1:0.8, place them in a tube furnace, and calcine at 750 °C for 25 h in an oxygen atmosphere with a heating rate of 5 °C / min. After natural cooling to room temperature, grind and pass through a 325-mesh sieve to obtain the No. 3 substrate, denoted as NaNi 0.4 Co 0.2 Mn 0.4 O2.
[0040] Grind and mix the nickel-cobalt-manganese series precursor NCM523 and the sodium source Na2CO3 in a molar ratio of 1:0.9, place them in a tube furnace, and calcine at 800 °C for 24 h in an oxygen atmosphere with a heating rate of 5 °C / min. After natural cooling to room temperature, grind and pass through a 325-mesh sieve to obtain the No. 4 substrate, denoted as NaNi 0.5 Co 0.2 Mn 0.3 O2.
[0041] Example 2
[0042] According to the composition of LaAl(PO4)2, weigh the corresponding masses of La(NO3)3·6H2O, NH4H2PO4, and Al(NO)3, add them to an appropriate amount of absolute ethanol, and ultrasonicate for 30 min to obtain a uniformly mixed suspension, denoted as coating material 1.
[0043] According to the composition of LaAl(PO4)2, weigh the corresponding masses of La2O3, Na3PO4, and Al(NO)3, add them to an appropriate amount of absolute ethanol, and ultrasonicate for 30 min to obtain a uniformly mixed suspension, denoted as coating material 2.
[0044] According to the composition of LaAl(PO4)2, weigh the corresponding masses of La(CH3COO)3, P2O5, and Al(NO)3, add them to an appropriate amount of absolute ethanol, and ultrasonicate for 30 min to obtain a uniformly mixed suspension, denoted as coating material 3.
[0045] According to the composition of LaFe(PO4)2, weigh the corresponding masses of LaCl3, H3PO4, and Fe2(SO4)3, add them to an appropriate amount of absolute ethanol, and ultrasonicate for 30 min to obtain a uniformly mixed suspension, denoted as coating material 4.
[0046] According to the composition of La3Li3(PO4)4, weigh the corresponding masses of La2(SO4)3, Na2HPO4, and CH3COOLi, add them to an appropriate amount of absolute ethanol, and ultrasonicate for 30 min to obtain a uniformly mixed suspension, denoted as coating material 5.
[0047] According to the composition of LaPO4, weigh the corresponding masses of La2(SO4)3 and (NH4)2HPO4, add them to an appropriate amount of absolute ethanol, and ultrasonicate for 30 min to obtain a uniformly mixed suspension, denoted as coating material 6.
[0048] According to the composition of AlPO4, weigh the corresponding masses of Al(NO)3 and NH4H2PO4, add them to an appropriate amount of absolute ethanol, and ultrasonicate for 30 min to obtain a uniformly mixed suspension, denoted as coating material 7.
[0049] According to the composition of Li3PO4, weigh the corresponding masses of CH3COOLi and NH4H2PO4, add them to an appropriate amount of absolute ethanol, and ultrasonicate for 30 min to obtain a uniformly mixed suspension, denoted as coating material 8.
[0050] According to the composition of FePO4, weigh the corresponding masses of Fe2(SO4)3 and NH4H2PO4, add them to an appropriate amount of absolute ethanol, and ultrasonicate for 30 min to obtain a uniformly mixed suspension, denoted as coating material 9.
[0051] Example 3
[0052] Weigh the No. 1 base material and coating material 1 according to the mass ratio of the base material to the coating material of 1:(0.0001 - 0.05). Put the base material into a ceramic mortar, pour the suspension mixed with the coating material into the mortar, and stir well at 50°C until the ethanol evaporates. Then put it into a vacuum oven and dry at 80°C for 3 h. After taking it out, grind it into a powder, put it into a porcelain boat, and calcine it in a tubular furnace at a calcination temperature of 550°C and a heating rate of 5°C / min in an O₂ atmosphere for 6 h to finally obtain the positive electrode active material 1.
[0053] Weigh the No. 2 base material and coating material 2 according to the mass ratio of the base material to the coating material of 1:(0.0001 - 0.05). Put the base material into a ceramic mortar, pour the suspension mixed with the coating material into the mortar, and stir well at 50°C until the ethanol evaporates. Then put it into a vacuum oven and dry at 80°C for 3 h. After taking it out, grind it into a powder, put it into a porcelain boat, and calcine it in a tubular furnace at a calcination temperature of 520°C and a heating rate of 5°C / min in an O₂ atmosphere for 7 h to finally obtain the positive electrode active material 2.
[0054] Weigh the No. 3 base material and coating material 3 according to the mass ratio of the base material to the coating material of 1:(0.0001 - 0.05). Put the base material into a ceramic mortar, pour the suspension mixed with the coating material into the mortar, and stir well at 50°C until the ethanol evaporates. Then put it into a vacuum oven and dry at 80°C for 3 h. After taking it out, grind it into a powder, put it into a porcelain boat, and calcine it in a tubular furnace at a calcination temperature of 540°C and a heating rate of 5°C / min in an O₂ atmosphere for 6 h to finally obtain the positive electrode active material 3.
[0055] Weigh the No. 4 base material and coating material 4 according to the mass ratio of the base material to the coating material of 1:(0.0001 - 0.05). Put the base material into a ceramic mortar, pour the suspension mixed with the coating material into the mortar, and stir well at 50°C until the ethanol evaporates. Then put it into a vacuum oven and dry at 80°C for 3 h. After taking it out, grind it into a powder, put it into a porcelain boat, and calcine it in a tubular furnace at a calcination temperature of 550°C and a heating rate of 5°C / min in an O₂ atmosphere for 7 h to finally obtain the positive electrode active material 4.
[0056] Weigh the No. 3 base material and coating material 5 according to the mass ratio of the base material to the coating material of 1:(0.0001 - 0.05). Put the base material into a ceramic mortar, pour the suspension mixed with the coating material into the mortar, and stir well at 50°C until the ethanol evaporates. Then put it into a vacuum oven and dry at 80°C for 3 h. After taking it out, grind it into a powder, put it into a porcelain boat, and calcine it in a tubular furnace at a calcination temperature of 560°C and a heating rate of 5°C / min in an O₂ atmosphere for 6 h to finally obtain the positive electrode active material 5.
[0057] Weigh the No. 2 base material and the coating material 6 according to the mass ratio of the base material to the coating material of 1:(0.0001 - 0.05). Put the base material into a ceramic mortar, pour the suspension mixed with the coating material into the mortar, and stir well at 50°C until the ethanol evaporates. Then put it into a vacuum oven and dry at 80°C for 3 hours. Take it out, grind it into powder, put it into a porcelain boat, and calcine it in a tube furnace at a calcination temperature of 580°C and a heating rate of 5°C / min in an O2 atmosphere for 6 hours to finally obtain the positive electrode active material 6.
[0058] Weigh the No. 1 base material and the coating material 7 according to the mass ratio of the base material to the coating material of 1:(0.0001 - 0.05). Put the base material into a ceramic mortar, pour the suspension mixed with the coating material into the mortar, and stir well at 50°C until the ethanol evaporates. Then put it into a vacuum oven and dry at 80°C for 3 hours. Take it out, grind it into powder, put it into a porcelain boat, and calcine it in a tube furnace at a calcination temperature of 550°C and a heating rate of 5°C / min in an O2 atmosphere for 6 hours to finally obtain the positive electrode active material 7.
[0059] Weigh the No. 1 base material and the coating material 8 according to the mass ratio of the base material to the coating material of 1:(0.0001 - 0.05). Put the base material into a ceramic mortar, pour the suspension mixed with the coating material into the mortar, and stir well at 50°C until the ethanol evaporates. Then put it into a vacuum oven and dry at 80°C for 3 hours. Take it out, grind it into powder, put it into a porcelain boat, and calcine it in a tube furnace at a calcination temperature of 550°C and a heating rate of 5°C / min in an O2 atmosphere for 6 hours to finally obtain the positive electrode active material 8.
[0060] Weigh the No. 1 base material and the coating material 9 according to the mass ratio of the base material to the coating material of 1:(0.0001 - 0.05). Put the base material into a ceramic mortar, pour the suspension mixed with the coating material into the mortar, and stir well at 50°C until the ethanol evaporates. Then put it into a vacuum oven and dry at 80°C for 3 hours. Take it out, grind it into powder, put it into a porcelain boat, and calcine it in a tube furnace at a calcination temperature of 550°C and a heating rate of 5°C / min in an O2 atmosphere for 6 hours to finally obtain the positive electrode active material 9.
[0061] Put the No. 1 base and an appropriate amount of absolute ethanol into a ceramic mortar, and stir well at 50°C until the ethanol evaporates. Then put it into a vacuum oven and dry at 80°C for 3 hours. Take it out, grind it into powder, put it into a porcelain boat, and calcine it in a tube furnace at a calcination temperature of 550°C and a heating rate of 5°C / min in an O2 atmosphere for 6 hours to finally obtain the positive electrode active material 10.
[0062] Performance Test
[0063] To verify the performance of the sodium-based layered oxide cathode active material of the lanthanum phosphate-coated sodium nickel cobalt manganese-based substrate provided by the present invention, the technical personnel tested the performance of the cathode active material obtained in Example 3.
[0064] I. Microscopic Morphology
[0065] In this experiment, the microscopic morphology of the cathode active material 1 was observed by scanning electron microscopy. The SEM images of the product at the scales of 3 μm and 1 μm are respectively as Figure 1 and Figure 2 shown. It can be observed from the SEM images that the samples before and after modification have similar spherical morphologies. The particle size of the uncoated sample is about 10 μm. After secondary calcination, the primary particle size of the coated sample becomes smaller as a whole, about 5-6 μm, but the secondary particles become significantly larger and the surface becomes rough. This is caused by the chemical reaction of the formation of the lanthanum phosphate coating layer during secondary calcination.
[0066] To further observe the detailed microscopic structure information, Figure 3 the transmission electron microscope (TEM) image of the cathode active material 1 is shown. The particle morphology shown by TEM is consistent with that shown by SEM, showing a well-crystallized O3-type layered structure. The interplanar spacing is 0.265 nm, which is highly consistent with the (104) crystal plane. In the TEM image, an ultrathin and uniform LaAl(PO4)2 coating with a thickness of about 4 nm can be clearly observed, and the original O3-type layered structure is hardly damaged, proving the success of surface coating modification.
[0067] II. Electrochemical Characteristics
[0068] In this experiment, first, the cathode active materials 1-9 prepared in Example 3 were homogenized and coated with polyvinylidene fluoride and acetylene black according to a mass ratio of 88:6:6. The obtained slurry was coated on an aluminum foil and dried in a vacuum oven at 80 °C for 5 h to make a pole piece. Among them, the mass loading of the cathode active material in the pole piece is about 3.0 ± 0.15 mg cm -2 .
[0069] Then, a metal sodium sheet was used as the counter electrode, a glass fiber was used as the separator, and a solution of ethylene carbonate (EC) and diethyl carbonate (DEC) containing 1 mol / L sodium perchlorate (the volume ratio of EC to DMC is 1:1) was used as the electrolyte to prepare a CR2032-type button battery in a glove box filled with Ar.
[0070] Next, the battery was cycled at a rate of 0.1C in a constant current mode within a voltage range of 1.5-4.2 V relative to Na / Na + , where 1C = 150 mA·h / g, and the charge-discharge performance test was carried out on a blue electric system.
[0071] Among them, the electrochemical tests were carried out under the condition of 25 °C in an incubator. The test method for the initial charge / discharge specific capacity of the first cycle was as follows: Constant current charging was carried out at a charging rate of 0.1C until 4.2V, and then discharging was carried out at a discharging rate of 0.1C until 1.5V. The test results of the 0.1C discharge specific capacity are shown in Table 1; the test method for the rate performance was as follows: Charge and discharge tests were carried out for 5 cycles each between 1.5 - 4.2V at the rates of 0.2C - 0.5C - 1C - 2C - 5C - 0.2C; the test method for the cycle performance was as follows: Activation was carried out by charging and discharging at 0.1C, and then charging at 0.2C and discharging at 1C for 100 cycles. The test results of the cycle retention rate are shown in Table 1;
[0072] Table 1: Comparison of Electrochemical Characteristics of Different Electrode Samples
[0073]
[0074]
[0075] Combined with the data in Table 1, first, by comparing Sample 10 with Samples 1 - 9, it can be found that the initial discharge specific capacity of the uncoated positive electrode at 0.1C is 150.5 mAh / g, which is significantly lower than that of the coated positive electrodes of Samples 1 - 9. The improvement in the initial discharge is attributed to La 3+ 、Al 3+ 、Li + 、Fe 3+ all being ionic conductor materials, and appropriate introduction will effectively improve the conductivity of the matrix material; secondly, by comparing Control Group Samples 7, 8, 9 with Experimental Group Samples 1 - 6 respectively, it can be found that the first discharge specific capacity and cycle capacity retention rate of the positive electrode coated with lanthanide phosphate are generally significantly higher than those of Samples 7 - 9. This is reasonably attributed to the fact that there is a strong covalent bond between PO4 3- and La 3+ in the lanthanide material, which provides better chemical stability for the positive electrode, reduces polarization, and inhibits the generation of phase transformation; finally, by comparing Samples 1 - 6 of the experimental group, it can be found that the double-metal coating layer has the best effect on improving the conductivity of the material. The reasonable combination of La 3+ with Al 3+ 、Li + 、Fe 3+ has the most significant effect on the improvement of the electrochemical performance, and improves the migration rate of Na + at the interface.
[0076] III. Residual Alkali Content
[0077] In this experiment, the residual alkali content of the 10 electrode materials in Example 3 before and after coating was measured and calculated by the indicator titration method. The test method was as follows:
[0078] Weigh 3 g of the sample and dissolve it in 100 mL of ethylene glycol. Stir and mix for 5 - 20 min until evenly mixed. Filter the mixed solution by suction. Take the filtrate, add phenolphthalein indicator, and titrate it with hydrochloric acid with a concentration of 0.05 mol / L to calculate the consumption of hydrochloric acid. Then take the filtrate again, add methyl chloride - bromocresol green mixed indicator, and titrate it with hydrochloric acid with a concentration of 0.05 mol / L to calculate the consumption of hydrochloric acid. Calculate the residual alkali content of the sample before and after coating through the consumption of hydrochloric acid.
[0079] In this experiment, the final results are shown in Table 2.
[0080] Table 2: Comparison of Residual Alkali Content of Different Electrode Samples
[0081]
[0082]
[0083] By analyzing the data in the chart, it can be found that:
[0084] The original sample contains CO3 2- with a content of 21.4 wt%, and OH - with a content of 0.28 wt%. After coating with different materials, the detected CO3 2- content and HCO 3- content in the sample both decrease significantly. The consumption of residual alkali solves the gelation phenomenon in the mixed slurry coating process.
[0085] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, and improvements made within the spirit and principles of the present invention shall be included within the protection scope of the present invention.
Claims
1. A sodium layered oxide positive electrode active material, the preparation method of which is: Mix the nickel-cobalt-manganese series precursor Ni a Co b Mn c (OH)2 and the sodium source material by grinding and mixing them in a molar ratio of 1:(0.8 - 1.1), calcine them at a temperature of 700 - 800 °C in an oxygen atmosphere for no less than 24 h, and after naturally cooling to room temperature, grind and sieve them to obtain the matrix material; among them, a+b+c=1; According to the composition of LaAl(PO4)2, LaLi3(PO4)4 or LaFe(PO4)2, La 3+ source material, PO4 3- source material and any one of aluminum nitrate, lithium acetate, and iron sulfate are jointly added to absolute ethanol, and ultrasonically mixed evenly to obtain a suspension for forming a coating material; According to the mass ratio of the base material to the coating material of 1: (0.0001 ~ 0.05), the base material is added to an appropriate amount of the suspension, fully stirred until the ethanol evaporates, and then vacuum dried and ground into powder; finally, calcined at a temperature of 520-580 ° C for not less than 6 hours in an oxygen atmosphere to obtain the desired sodium layered oxide positive electrode active material.
2. The sodium layered oxide cathode active material according to claim 1, characterized in that: The composition of the matrix material is Na x Ni a Co b Mn c O2, where 0.8 ≤ x ≤ 1 and a + b + c = 1.
3. The sodium-layered oxide cathode active material according to claim 1, characterized in that: The coating material is LaAl(PO4)2.
4. The sodium layered oxide cathode active material according to claim 1, wherein: The nickel-cobalt-manganese series precursor Ni a Co b Mn c (OH)2 is any one of NCM622, NCM811, NCM424, and NCM523.
5. The sodium layered oxide cathode active material according to claim 1, characterized in that: The sodium source material is NaOH or Na2CO3; The La 3+ source material is any one of lanthanum nitrate hexahydrate, lanthanum chloride, lanthanum sulfate, lanthanum oxide or lanthanum acetate; The PO4 3- The source material is any one of phosphoric acid, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate or phosphorus pentoxide.
6. The sodium-layered oxide cathode active material according to claim 5, wherein: The coating material is prepared from lanthanum nitrate hexahydrate, aluminum nitrate and ammonium dihydrogen phosphate in a molar ratio of 1:1:
2.
7. The sodium layered oxide cathode active material according to claim 1, wherein: The heating rate during the calcination of the matrix material and the final product was 5 °C / min; The temperature of the base material and the suspension is controlled at 50-60°C during the stirring stage, and the temperature is controlled at 80-85°C during the vacuum drying stage.
8. The sodium-layered oxide cathode active material according to claim 1, characterized in that: It comprises a matrix material and its surface coating material, and the mass ratio of the two is 1:(0.0001 to 0.05); the composition of the matrix material is Na x Ni a Co b Mn c O2, 0.8 ≤ x ≤ 1, a + b + c = 1, O3 phase structure; the composition of the coating material is LaAl(PO4)2, La3Li3(PO4)4 or LaFe(PO4)2.
9. A cathode material for a sodium-ion battery, characterized in that, The invention is prepared by uniformly mixing polyvinylidene fluoride, acetylene and the sodium-electrolyte layered oxide positive electrode active material as claimed in any one of claims 1 to 7 in a ratio of 6:6:
88.
10. A sodium-ion battery, characterized in that, The method uses a sodium metal sheet as a counter electrode, glass fiber as a diaphragm, and a 1:1 volume ratio solution of ethylene carbonate and diethyl carbonate containing 1 mol / L sodium perchlorate as an electrolyte. And coating the slurry corresponding to the positive electrode material of the sodium-ion battery as described in claim 9 onto an aluminum foil, and making a pole piece after vacuum drying; the mass loading of the sodium-based layered oxide positive electrode active material in the pole piece is 3.0 ± 0.15 mg / cm -2 .